EXPLORING DIGITAL LITERACY USAGE FOR SELF-DIRECTED LEARNING: RURAL ADOLESCENTS"™ PERSPECTIVES - Susanti, Meli; Nurhayati, Sri (Jurnal Visi Ilmu Pendidikan, 2024)
This study aims to address this gap by examining rural adolescents' perspectives on the use of digital literacy in self-directed learning and its potential to transform rural education. The research employed a qualitative approach and involved in-depth interviews with thirty rural adolescents. The findings indicate that rural adolescents perceive themselves to have good digital literacy skills and actively use digital media for learning. They recognise the benefits of digital literacy in accessing information, collaborating with others, and overcoming learning barriers. The study underscores the significance of digital literacy in empowering rural adolescents to take charge of their education and navigate the digital landscape. These findings have implications for educators and policymakers in promoting digital literacy in rural areas to ensure equitable access to high-quality education. Future research should further investigate the intersection of digital literacy and self-directed learning among adolescents to enhance educational outcomes in an increasingly digital world.